2014
DOI: 10.4081/ijas.2014.3357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Grape Seed Proanthocyanidins on Growth Performance, Some Serum Biochemical Parameters and Body Composition of Tilapia (Oreochromis Niloticus) Fingerlings

Abstract: The present study was performed with tilapia (Oreochromis niloticus) to evaluate the effects of diet supplementation with grape seed proanthocyanidins (GSPs) on fish growth performance, some serum parameters and body composition. Three hundred tilapia fingerlings with the initial average body weight of 8.25±0.07 g were randomly divided into five treatment groups with four replicates in each group and 15 fish in each replicate. The dietary GSPs levels of five treatment groups were 0 (control group), 200, 400, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 28 publications
11
44
0
Order By: Relevance
“…According to the results of the present study, growth performance of common carp in terms of FCR and weight gain was significantly improved at 400 mg kg -1 level of polyphenols in canola meal based diet. Our findings are in accordance with the results reported by Zhai et al (2014) who noted lowest FCR (1.31) and improved growth performance in Nile tilapia fed diets supplemented with the antioxidant, grape seed proanthocyanidins (GSP) at levels of 400 and 600 mg kg -1 .…”
Section: Discussionsupporting
confidence: 93%
“…According to the results of the present study, growth performance of common carp in terms of FCR and weight gain was significantly improved at 400 mg kg -1 level of polyphenols in canola meal based diet. Our findings are in accordance with the results reported by Zhai et al (2014) who noted lowest FCR (1.31) and improved growth performance in Nile tilapia fed diets supplemented with the antioxidant, grape seed proanthocyanidins (GSP) at levels of 400 and 600 mg kg -1 .…”
Section: Discussionsupporting
confidence: 93%
“…Lots of AST and ALT would be emitted into the blood when liver function is damaged. Therefore, serum AST and ALT are used as important indicators to reflect the liver function of the fish (Zhai, Lu, & Chen, ). In our study, serum AST and ALT activities were decreased with the increasing dietary FA levels, indicating that a better trend occurred in the liver of the tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…When liver function is damaged, much ALT and AST would be emitted into the blood. As a result, ALT and AST are two commonly measured enzymes and/or sensitive indicators of hepatocellular damage (Zhai, Lu & Chen ). In the present study, lower serum TG, TCHO and LDLC, and higher HDLC levels were observed in FA‐ or FA derivative‐supplemented fish when compared to unsupplemented ones.…”
Section: Discussionmentioning
confidence: 99%